Pemodelan Spasial Arah Penyebaran Kebakaran Hutan Dengan Menggunakan Penginderaan Jauh Dan Sistem Informasi Geografis Di Taman Nasional Baluran Kabupaten Situbondo Provinsi Jawa Timur Bulan Oktober Tahun 2014 - Setyawan, Didik; , Drs. Yuli Priyana, M.Si; , Agus Anggoro Sigit, S.Si, M.Sc (2015)
Forest fires is one of the more common disorders. The negative impact caused by forest fires is large enough so that prevention since the beginning needs to be done in handling forest fires. One of them using remote sensing technology and geographic information systems. This research aims to: 1) Determine the potential distribution of forest fires in the area Baluran National Park. 2) Modeling spatial of direction spreading forest fire in the area Baluran National Park October 2014. The method used in this research is secondary data analysis methods include the analysis of each parameter data in October 2014. All of the parameters such as rainfall, surface soil temperature, distance roads to the forest, and land cover is used as the principal parameter in the arrangement forest fires hazard map. The map is a reference after combined with wind direction data for modeling direction spreading of forest fire. Model direction spreading of forest fire in Baluran National Park on October 2014 toward to the east, south, and west. Forest fire spreading eastward when appear of hotspots in the north. While spreading towards the south when appear of hotspots in the east and south. Forest fires also spreading towards the west when appear of hotspots in the Baluran National Park west and north.